Eco-friendly piassava fiber reinforced composite for high performance coating application - de Carvalho, Juliana Peixoto Rufino Gazem; Lopes, Felipe Duarte; Simonassi, Noan Tonini; Monteiro, Sérgio Neves; Carvalho, Eduardo Atem de; Vieira, Carlos Maurício Fontes (REVISTA CEREUS, 2020)
High performance coatings (HPC) may be used as floors, made by mixing substrates with resin which are today applied in several types of floors by the Brazilian industries. The application of HPC floors is associated with some benefits such as speed of application, high mechanical performance and absence of expansion joints. The Brazilian standard requires that the manufacture of HPC uses epoxy resin and mineral aggregates. This work, however, aimed to study the mechanical performance of a similar material, made by using a castor oil based polyurethane resin, instead of epoxy, mixed with ground piassava natural fibers and determine if it is possible to use as a novel HCP. The piassava fibers were obtained as an industrial waste of a broom factory located in Campos dos Goytacazes, Brazil. A preliminarily characterization of the fibrous waste was carried out to determine its density and the fibers were subjected to a morphological analysis through scanning electron microscopy (SEM). The water absorption and compressive strength of the novel HPC were determined and the fracture surface was observed by SEM. The results proved the effectiveness of using 20% fiber, which made possible to apply this composition as HPC.